ANALYSIS OF THE FATWA MECHANISM OF DSN-MUI APPLICATION NO. 29 / DSN-MUI / VI / 2002 HAJJ CREDIT FINANCING IN ISLAMIC FINANCIAL INSTITUTIONS - Paramita, Sinta; Ibdalsyah, Ibdalsyah; Hakiem, Hilman (Al-Infaq: Jurnal Ekonomi Islam, 2017)
Fatwas authority on sharia economy in Indonesia is under the National Sharia Council of Majelis Ulama Indonesia (DSN-MUI). The existence of DSN-MUI outside the central bank structure makes the fatwa authority independent, more credible and nationally recognized in issuing decisions and fatwas related to sharia issues faced by banks and other Islamic financial institutions. In some sharia banks there are different practices. Especially for the management of pilgrimage involving many sectors in it how compliance with the fatwa which has been determined by the National Sharia Council. Though banks are basically not only as a place to seek profit or invest for this world alone but as a way to get closer to Allah SWT. This research will examine the application of Fatwa DSN-MUI No.29 / DSN-MUI / VI / 2002 about Hajj Credit Financing by Islamic Finance Institutions at PT. BPRS Amanah Ummah Leuwiliang Bogor. Research use qualitative approach method with type of qualitative empirical research. The results from this study are administration service of pilgrimage and hajj credit financing on cost of hajj travel in BPRS Amanah Ummah for both features and product details based on sharia is permitted in accordance with the Fatwa DSN-MUI. 29 / DSN-MUI / VI / 2002 about Hajj credit financing in Islamic financial institution. PT. BPRS Amanah Ummah is expected to seek a better system, modern and practical in packing this product. Thus, it can attract prospective customers or prospective pilgrims.